The Role of Innovation on Inmate Rehabilitation and Reintegration in Africa - Excellence-oluye, Nchekwube; Dunbar, Triumphant; Makinde, Damilola Ayomiposi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Inmate rehabilitation and reintegration remain critical challenges in Africa’s prison systems, with traditional approaches often failing to equip ex-offenders with the skills and support needed for successful societal reentry. This paper examines the role of innovation in enhancing rehabilitation and reintegration efforts, focusing on technology-driven education, vocational training, and entrepreneurial initiatives within correctional facilities. Drawing on institutional theory, it explores how systemic reforms and leadership in prison administration can foster more effective rehabilitation strategies. By analyzing secondary data and existing models of innovative prison programs, this study highlights best practices and policy recommendations that can reduce recidivism and promote sustainable development. The findings contribute to the discourse on integrating technology and leadership in criminal justice reform, offering pathways for Africa to adopt more inclusive and forward-thinking rehabilitation frameworks.